Epidemiological survey of equine influenza in Andalusia, Spain - Jurado-Tarifa, E.; Daly, J.M.; Pérez-Écija, A.; Barba-Recreo, M.; Mendoza, F.J.; Al-Shuwaikh, A.M.; García-Bocanegra, I. (Elsevier, 2018)
Equine influenza is a highly contagious respiratory disease considered the most important respiratory disease in equids. Although influenza A virus (IAV) has caused outbreaks in equids worldwide, surveillance on these species in Spain has not been conducted. A cross-sectional study was carried out to determine the individual and herd prevalence of antibodies against H3N8 and H7N7 IAV in equids in Andalusia (southern Spain). Antibody against IAV was measured by the single radial haemolysis assay. A spatial scan statistical analysis was carried out using a Bernoulli model. Risk factors associated with IAV infection were assessed by multivariate analysis. Antibodies to H3N8 IAV were detected in 241 out of 464 unvaccinated equids (51.9%; 95% CI: 47.4–56.5). Seropositivity against the H7N7 subtype IAV was not found in any of the analysed animals. Significantly higher seropositivity was found in geriatric (OR= 6.1, P = 0.008, 95% CI= 1.6 – 23.1) and adult (OR= 4.8, P < 0.001, 95% CI= 2.5 – 9.0) equids compared to young. Specific antibodies against A/equine/Shropshire/2010 (H3N8) or A/equine/Newmarket/5/2003 (H3N8) only were confirmed in 11 and 45 of the animals, respectively. The spatial analysis showed a statistically significant cluster centred in the west part of Andalusia. The results confirmed widespread H3N8 subtype IAV exposure in equine species in Andalusia. Conversely, the absence of seropositivity against H7N7 IAV obtained in the present study suggests that this subtype has not circulated in southern Spain in recent years. Because of the animal health and economic consequences of IAV in equids, further surveillance and molecular studies are required to monitor and characterize the most prevalent IAV circulating in these species in Spain.